PENGARUH STORE ATMOSPHERE, KELENGKAPAN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO ALTEK BANGUNAN DI SITUBONDO - Bulu, Orviana; Subaida, Ida; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The Altek Gedung shop is a business that operates in the field of selling building materials. The purpose of this research is to analyze and test the influence of store atmosphere, product completeness and price on purchasing decisions with consumer satisfaction as an intervening variable at the Altek Bangunan Store in Situbondo. The population in this research is consumers of the Altek Gedung Store. Data analysis and hypothesis testing in this research used the Partial Least Squares Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Store atmosphere has a positive but not significant effect on consumer satisfaction, Product completeness has a significant positive effect on consumer satisfaction, Price has a significant positive effect on consumer satisfaction, Store atmosphere has a positive but not significant effect on decisions. purchasing, Product completeness has a positive but not shignificant effect on purchasing decisions, Price has a negative but not significant effect on purchasing decisions, Consumer satisfaction has a significant positive effect on purchasing decisions, Store atmosphere has a positive but not significant effect on purchasing decisions through consumer satisfaction, Product completeness has a significant effect positive effect on purchasing decisions through consumer satisfaction. Price has a significant positive effect on purchasing decisions through consumer satisfaction.